The linkage between β1 integrin and the actin cytoskeleton is differentially regulated by tyrosine and serine/threonine phosphorylation of β1 integrin in normal and cancerous human breast cells - Takahashi Kazuhide (BMC Cell Biology, 2001)
Abstract Background Structural requirements for the β1 integrin functions in cell adhesion, spreading and signaling have been well documented mainly for fibroblasts. In this study, we examined the reason for the reduced surface expression of β1 integrin in human breast cancer MCF-7 cells compared to normal human breast epithelial (HBE) cells, both of which adhered to collagen type IV. Results The β1 integrin immunoprecipitates from either HBE or MCF-7 cells involved α-actinin while actin coprecipitated with β1 integrin from HBE cells but not from MCF-7 cells. Immunoblotting using the anti-phosphotyrosine (PY) antibody indicated the phosphorylation of β1 integrin at least at tyrosine in both cells. Dephosphorylation of β1 integrin from HBE cells by protein tyrosine phosphatase (PTP), but not by protein serine/threonine phosphatase (PP), caused dissociation of actin from β1 integrin, although dephosphorylation of it from MCF-7 cells by either PTP or PP caused association of the two proteins. In MCF-7 cells β1 integrin coprecipitated doublet of proteins having the Ca2+/calmodulin-dependent protein kinase (CaMK) II activity that was susceptible to KN-62, a specific inhibitor of CaMKII. Conclusion The results suggest that β1 integrin is tyrosine phosphorylated and links with actin via α-actinin in HBE cells but prevented from linking with actin in MCF-7 cells by phosphorylation at both tyrosine and serine/threonine of β1 integrin which forms a complex with α-actinin and CaMKII. Thus the linkage formation of β1 integrin with actin may be differentially regulated by its tyrosine and serine/threonine phosphorylation in normal HBE cells and breast cancer MCF-7 cells.